Determinants of stock returns in property and real estate companies listed on the Indonesia Stock Exchange - Sutresna Arinto; Prima Naomi (Journal of Enterprise and Development (JED), 2024)
Purpose — This study aims to investigate the influence of macroeconomic factors, including economic growth, inflation, the rupiah exchange rate, and interest rates, as well as corporate financial performance indicators such as leverage and profitability, on the stock returns of Indonesian Property and Real Estate Sub-Sector companies.Method — The research data consists of annual data obtained from the Indonesia Stock Exchange, the Indonesia Central Bureau of Statistics, and Bank Indonesia for the period from 2017 to 2021. The research population comprises 36 Property and Real Estate companies listed on the Indonesia Stock Exchange. Out of these, 28 companies meet the sample requirements. The analysis employs panel data regression to examine the data.Result — The results indicate that inflation and exchange rates have a negative and statistically significant impact on stock returns. On the other hand, economic growth, interest rates, return on equity, and the debt-to-equity ratio exhibit a positive influence on stock returns, although these effects are not statistically significant.Contribution — This study's distinctive contribution is its focused analysis of the Property and Real Estate Sub-Sector in Indonesia. It stands out by exploring the intricate relationship between macroeconomic factors and financial performance variables concerning the stock returns of companies within this sub-sector. This nuanced approach provides valuable insights into a specific industry within the Indonesian market, shedding light on previously unexplored dynamics and contributing to a deeper understanding of how these factors affect stock returns in this context.